The etiology of attention deficit disorder with hyperactivity: A protocol for an umbrella review - Wenhao Su; Hairong Jia; Luo Yang; Jiaqi Zhang; Zhaoyang Wei; Pepertual Tsikwa; Yanru Wang (PLoS ONE, 2025)
Introduction Attention deficit hyperactivity disorder (ADHD) is one of the common neurodevelopmental disorders and is widely prevalent worldwide. The primary symptoms of ADHD include inattention, impulsivity, and hyperactivity, which significantly impact the cognitive, behavioral, and emotional dimensions of individuals. These disorders often continue throughout adulthood and, along with associated complications, affect various domains such as personal health, academic achievement, and social interactions. The pathogenesis and contributing causes of ADHD remain unclear at present. Therefore, this study aims to perform an umbrella review of systematic reviews and meta-analyses (SRMAs) to systematically assess the quality of methodologies, potential biases, and validity of all epidemiological evidence related to risk factors for ADHD while offering a comprehensive summary of the evidence regarding these risk factors. Methods and analysis This study follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) and Cochrane Handbook. We will systematically search 6 databases, including The Cochrane Library Central, PubMed, Embase, Web of Science, CINAHL, and Scopus from the initial period up until 2024 (last update). We will assess the quality of the included SRMAs using the tool to assess risk of bias in systematic reviews (ROBIS), the methodological quality of systematic reviews (AMSTAR)-2, PRISMA-2020, and the grade of recommendations assessment, development and evaluation (GRADE). Two authors will use the ecological models of health behavior to classify the causes and risk factors of ADHD. Finally, we will provide descriptive and comprehensive recommendations for clinical practice and future research. Trial registration PROSPERO (CRD42024597126).